CADAVERIC STUDY OF ANATOMICAL VARIATION OF SCIATIC NERVE IN POPULATION OF BIHAR AND ITS CLINICAL APPLICATION: A CROSS-SECTIONAL STUDY. - Sinha, Arti; Nandini, Vijay; Prasad, Rashmi; Mahaseth, Shyam Narayan (Student’s Journal of Health Research Africa, 2024)
Background The sciatic nerve is the largest in the body. It has peroneal and tibial components. The sciatic nerve (SN) leaves the pelvis through the larger sciatic foramen under the Piriformis muscle (PM) to become the tibial nerve. After that, the sciatic nerve crosses between the pelvic ischial tuberosity and the bigger femur trochanter, ending at the popliteal fossa. Aim- Cadaveric research was undertaken to ascertain the differences in the anatomy of the sciatic nerve. Methods A cross-sectional investigation was done in 50 equally divided anatomical cadavers of both genders to determine the occurrence of anatomical variations in the SN exit associated with the PM. One of the methods used to acquire the data from the bodies of equal males and females involved dissecting 100 SN. The gluteal regions of the cadavers had to be in ideal condition and have been kept adequately to enable data collection and dissection, which was one criterion for inclusion. Results The study included 52% males and 48% females. The sciatic nerve exited inferior to the PM in 90% of limbs, inferiorly and between the PM’s fascicles in 6%, and superiorly and between the fascicles in 4%. Unilateral abnormalities were 12% more common on the left side and 12.5% more frequent in females than males. The SN most often branched in the popliteal fossa (54%), followed by the gluteal region (38%) and the middle third of the thigh (8%). Conclusion This study highlights the anatomical variations between the SN and PM, which are crucial for clinical and surgical procedures. Awareness of these variations can enhance diagnostic accuracy and surgical outcomes, particularly in the context of SN-related conditions and interventions. Recommendation Further large-scale, multicenter studies are recommended to confirm these findings and provide more comprehensive insights into SN anatomical variations’ prevalence and clinical implications.